DEALING WITH AUTHENTICITY IN THE CONSERVATION AND RESTORATION OF WALL PAINTINGS AND ARCHITECTURAL SURFACES - Ursula Schädler-Saub (Ochrona Dziedzictwa Kulturowego)
Authenticity is a key term in the modern theory and practice of heritage preservation. The great influence of this term began with the Venice Charter and increased in the following decades until this day, as numerous documents and publications have dealt with issues concerning the concept and significance of authenticity. However, the term is characterized by a certain vagueness, despite its central role in the international debate. This article presents three case studies related to the conservation-restoration of wall paintings and architectural surfaces in Germany and Italy and uses them to clarify some central theoretical issues, intertwining them with practical needs and demands. The multi-layered meanings of authenticity in the practice of conservation-restoration can range from the respectful preservation of the handed-on conditions and appearance of a work, with all material remains of its reception and interpretation, to the critical evaluation of historical restorations based on scholarly value judgments, and even to the reconstruction e. g. of architectural surfaces as a method for the sustainable protection of historical findings and a good way to visualize historical presentations and hand on traditions of craftmanship. For such a broad spectrum of meanings, the term authenticity can become a helpful umbrella term in interdisciplinary and transdisciplinary communication, well-known and appreciated by all experts and by the public. In order to avoid the use of the term authenticity as a catch-all that can mean everything or nothing, the relationship with case studies can bring awareness about the broad palette of these approaches and how the theory and practice of heritage preservation are always interconnected.